deriving scf - Prepared by Mikhail Pevzner Assets t =...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
Prepared by Mikhail Pevzner ) 2 ( ) 1 ( 1 1 1 - - - + = + = t t t t t t Equity s Liabilitie Assets Equity s Liabilitie Assets Subtracting equation (2) from equation (1) implies that ) 3 ( t t t Equity s Liabilitie Assets + = Since Assets=Cash+Non-cash Assets (4), substituting equation (4) in equation (3) implies that: Equity s Liabilitie Assets Noncash Cash + = + (5) Therefore: Equity s Liabilitie Assets Noncash Cash + + - = (6) But… Non-cash Assets=Non-cash current assets+Non-cash non-current assets (7) Liabilities=Current Liabilities+Non-current liabilities (8) Equity=Capital Stock+Retained Earnings (9) Thus, expanding equation (6) further, we obtain: Equity s liabilitie Noncurrent s Liabilitie Current assets noncurrent Noncash assets current Noncash Cash + + + + - = (11) However, Equity= Capital Stock+Net Income-Dividends (12). Hence,
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Image of page 2
This is the end of the preview. Sign up to access the rest of the document.

Page1 / 3

deriving scf - Prepared by Mikhail Pevzner Assets t =...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online